A narrative analysis of learning to teamwork in youth sport: a sociocultural perspective on communication and cooperative learning - Arumí-Prat, Joan; Pla-Campas, Gil (Frontiers in Sports and Active Living, 2025)
This study investigates from a sociocultural perspective how team members' communication within a training approach based on cooperative learning (CL) fosters the development of teamwork. Employing a narrative analytic approach, the research examines into the experiences of a coach and his players in the locker room conversations before, during and after the game, throughout the season. A total of 69 5- to 17-minute conversations were recorded and transcribed over 23 matches that took place during an entire season. Three different steps were implemented for the narrative analysis: codification of the dialogues under the CL approach, identification of stages of learning in players and creation of the autoethnographic storytelling. Findings are shown through a narrative based on five significant stories that illustrate the context, and the complex dynamics of social interaction that emerge to learn teamwork in youth sport are discussed. By examining the coach's adoption of CL principles as a coaching and communication approach between team members, this research shows how these principles frame the learning context and contribute to teamwork. This research reveals the complexities of player-coach interactions and provides valuable insights for youth team sport coaches committed to fostering teamwork.